2010
DOI: 10.1558/jmea.v23i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Political Geography and Palatial Crete

Abstract: The political geography of Crete during the period of the Bronze Age palaces has been a subject of widespread debate, not only with respect to the timing of the island's move towards greater social and political complexity, but also with regard to the nature of the political institutions and territorial configurations that underpinned palace--centred society, as well as their longer--term stability over the course of the 2 nd millennium BC. As such, the region provides an ideal context in which to consider the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 13 publications
0
16
0
4
Order By: Relevance
“…Collapse at the end of the Neopalatial period-defined as Middle Minoan III until the end of Late Minoan IB, perhaps some 250 years to c. 1450 BC (but see Bruins 2010;Dickinson in press;Manning 2010;Manning et al 2006;Ramsey et al 2010)-is identified by the end of a palace-based culture that used Linear A script and the integrated islandwide system that had developed over time (Davis 2008;Manning 2008;Schoep 2010;Tomkins and Schoep 2010), perhaps with some form of Knossian pre-eminence (Bevan 2010). This was accompanied by widespread but selective destruction by fire, abandonments, deurbanization, and possible depopulation (Hallager 2010, p. 153).…”
Section: Palatial (Minoan) Cretementioning
confidence: 99%
“…Collapse at the end of the Neopalatial period-defined as Middle Minoan III until the end of Late Minoan IB, perhaps some 250 years to c. 1450 BC (but see Bruins 2010;Dickinson in press;Manning 2010;Manning et al 2006;Ramsey et al 2010)-is identified by the end of a palace-based culture that used Linear A script and the integrated islandwide system that had developed over time (Davis 2008;Manning 2008;Schoep 2010;Tomkins and Schoep 2010), perhaps with some form of Knossian pre-eminence (Bevan 2010). This was accompanied by widespread but selective destruction by fire, abandonments, deurbanization, and possible depopulation (Hallager 2010, p. 153).…”
Section: Palatial (Minoan) Cretementioning
confidence: 99%
“…Thus, the explosion of settlements in the Protopalatial period is largely seen as part of the emergence of a palatial system (Nowicki 1999;Sbonias 1999), and an observed decline in overall site numbers in the subsequent Neopalatial period as a process of nucleation, and a further concentration of power at a limited number of palaces, indeed conceivably with overall political authority concentrating at Knossos (Amato et al 2014: 131;Cunningham and Driessen 2004;Whitelaw in press). Although any political hierarchy probably requires "some form of hierarchical [spatial] ordering" (Bevan 2010: 28, see also Cherry 1986Cadogan 1994;Cunningham and Driessen 2001;cf. Manning 1995;Knappett 1999;Adams 2006 who distinguish different kinds of power), this ordering is dependent on the scale and form of the interaction.…”
Section: Bronze Age State Formationmentioning
confidence: 99%
“…This method belongs to a set of multi-scalar spatial statistics such as K functions that summarise second-order effects of spatial patterns at multiple scales(Orton 2004: 303). These have not been particularly common in archaeological studies (but seeBevan and Conolly 2006, 2009; Bevan et al 2013a; Sayer and Wienhold 2012 for examples). 5 A 95% critical envelope was used, which conservatively removes the most extreme PCF results.…”
mentioning
confidence: 99%
“…This has recently been re-examined critically, using GIS techniques to update the Thiessen polygon approach with modelled walking time, dividing central Crete among the three known early and principal palaces (Bevan 2010). But is this how people actually interact across the Cretan landscape?…”
Section: Topography and Territoriesmentioning
confidence: 99%